POTTERY PRODUCTION CENTER (6TH – EARLY 7TH C.) IN THE CITY OF SOFIA, LOZENETS RESIDENTIAL DISTRICT – YUZHEN (SOUTH) PARK. STUDIES IN 2000 – 2001 - Metodi Daskalov (Приноси към българската археология)
The current paper aims at presenting the results from the 2000 – 2001 excavations at Lozenets residential district – Yuzhen (South) Park, Sofia. The remains of a church from the 340s – 350s were documented. This church functioned until the late 410s. Later on, the site used to be a significant architectural complex composed of a single-apse, three-nave basilica surrounded by walls with towers at the corners that also held massive buildings southwest of the basilica’s narthex and atrium courtyard. The complex was built immediately after the first decade of the 5th c. and functioned in this initial form until nearly the end of the same century. Certain changes due to tumultuous circumstances occurred before the end of the century. Subsequent reconstructions of the complex were carried out around the middle of the 6th c. These changes probably indicate that the complex was losing its religious functions and that a lay population had settled in the enclosed space.